A New Two-Component Model for Hadron Production in Heavy-Ion Collisions - Xuejiao Yin; LiLin Zhu; Hua Zheng (Advances in High Energy Physics)
Using the experimental data from the ALICE program on the centrality dependence of the transverse momentum (pT) spectra in Pb+Pb collisions at sNN=2.76 TeV, we show that the double-Tsallis distribution and the generalized Fokker-Planck (FP) solution cannot describe the spectra of pions, kaons, and protons from central to peripheral collisions in the entire pT region, simultaneously. Hence, a new two-component distribution, which is a hydrodynamic extension of the generalized FP solution accounting for the collective motion effect in heavy-ion collisions, is proposed in order to reproduce all the identified particle spectra. Our results suggest that the particle production dynamics may be different for different particles, especially at very low pT region.